2005
DOI: 10.1038/sj.ejcn.1602309
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate juice supplementation in chronic obstructive pulmonary disease: a 5-week randomized, double-blind, placebo-controlled trial

Abstract: Objective: The aim of the present study is to investigate the effect of antioxidant polyphenol-rich pomegranate juice (PJ) supplementation for 5 weeks on patients with stable chronic obstructive pulmonary disease (COPD), since the oxidative stress plays a major role in the evolution and pathophysiology of COPD. Design: A randomized, double-blind, placebo-controlled trial was conducted. Subjects: A total of 30 patients with stable COPD were randomly distributed in two groups (15 patients each). Interventions: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
107
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 40 publications
8
107
0
Order By: Relevance
“…In fact, urolithins appear in blood, urine, and feces of human volunteers 12-24 h after consumption of a single dose of several ET-rich foods and persist in vivo for up to 48-56 h after ingestion (9)(10)(11)(12). Despite these advances in understanding ET metabolism in rodents (13,14) and humans (9-12), there have been no studies determining the disposition of ET metabolites to tissues of interest including the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, urolithins appear in blood, urine, and feces of human volunteers 12-24 h after consumption of a single dose of several ET-rich foods and persist in vivo for up to 48-56 h after ingestion (9)(10)(11)(12). Despite these advances in understanding ET metabolism in rodents (13,14) and humans (9-12), there have been no studies determining the disposition of ET metabolites to tissues of interest including the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] The herbs ivy leaf and plantain have been suggested for chronic bronchitis, but there is no meaningful evidence that they actually help. [42] One study failed to find pomegranate juice helpful for COPD.…”
Section: Plant-based Therapies For Copdmentioning
confidence: 99%
“…1, which are regarded as metabolites from tannins and related compounds. [6][7][8][9][10][11] The experiments revealed noticeable differences in the binding behavior due to subtle differences in the structures of the compounds as discussed below. droxybenzoic acid followed by methylation according to a previous report.…”
mentioning
confidence: 99%
“…Tannic acid, a gallotannin mixture, is metabolized into gallic acid and its further methylation gives 4-O-methylgallic acid (5-hydroxyisovanillic acid), 7,8) while metabolism of ellagitannins yields ellagic acid, or further reductive changes produce urolithin A (3,8-dihydroxy-6H-dibenzo[b,d]-pyran-6-one) and related compounds. [9][10][11] The present study thus treated the binding of those phenolic compounds shown in Fig. 1, which are regarded as metabolites from tannins and related compounds.…”
mentioning
confidence: 99%